Effect of Variation of SiC Mass Fraction on Mechanical Properties of Al-SiC Composite Using Stir Casting Method - Sumarji Sumarji; Naufal Fardio Albajili; Mahros Darsin; Rahma Rei Sakura; Andi Sanata (Journal of Mechanical Engineering Science and Technology (JMEST), 2022)
Al-SiC is a composite composed of AA6061 as a matrix and SiC as a reinforcement particle. The variation of mass added will affect the mechanical properties of the composite because Al-SiC is hardenable, which means that its mechanical properties can be improved by adding the reinforcement component. However, an excessive portion of SiC leads to a decrease in mechanical properties. The purpose of this study was to find the optimal composition of the addition of SiC into the aluminium matrix to gain maximum tensile strength and hardness. The mass fraction variation that would be used in this composite was the addition of 6%, 8%, and 10% SiC with the addition of 1% Mg as a wetting agent. The mixing process used the stir casting method. The process of adding SiC and Mg was carried out by melting the aluminium while stirring it for a certain time before it went to the furnace. The ASTM E8/E8M standard was used for observing the tensile strength of the specimens. Machining was carried out before testing. The specimens were also tested for hardness using the Rockwell hardness method. The result shows that the addition of SiC at the amount of 6%, 8%, and 10% SiC increased the ultimate tensile strength by154.10 MPa, 175.01 MPa, and 198.14 MPa, respectively. Similarly, the hardness also increased up to 30.1 HRF, 48.1 HRF, and 66 HRF, respectively. Microstructure observation also confirmed that a 10% SiC fraction results in less defect and good wettability. The addition of 10% SiC and 1% Mg resulted in maximum tensile strength and hardness and the best microstructure.